Charakterystyka antropologiczna zawartości popielnicy z Woli Łobudzkiej, stan. 1, gmina Szadek - Śmiszkiewicz-Skwarska, Alicja; Malinowski, Andrzej (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
The cinerary urn (grave 3) from a cementary of the Przeworsk cullure contained osseous materials (burnt human bones). The urn dates back to the Roman period. In the grave no anatomical order of bones was revealed. The following fragments of bones were separated: craniocerebral and craniofacial bones, fragments of teeth, bones of trunk, bones of upper and lower extremities. The analisis shows that above-mentioned relics may have belonged to a male, of flimsy stature, c. 171-175 cm high who died at the age of adultus (25-30).